UV-assisted water splitting of stable Cl-doped ZnO nanorod photoanodes grown via facile sol-gel hydrothermal technique for enhanced solar energy harvesting applications. (15th November 2019) - Sahoo, Pooja; Sharma, Akash; Padhan, Subash; Udayabhanu, G.; Thangavel, R.
Graphical abstract: Highlights: A photocurrent density of 2.16 mA cm −2 was observed for Cl-ZnO NRs. LHE of 97% has been achieved for the doped samples. Low recombination rate and better electron-hole separation were observed. Cl-ZnO NRs are envisioned to provide valuable platform for solar water splitting application. Abstract: Vertically aligned pristine ZnO and Cl-doped ZnO nanorod arrays were grown by a simple, cost-effective sol-gel and hydrothermal method. These nanorods (NRs) were fabricated to demonstrate their potential as highly efficient photoelectrodes to be used in photoelectrochemical water splitting applications. XRD measurements indicate that all the fabricated NRs have preferably grown along c-axis (0 0 2) direction. FESEM images confirmed hexagonal shaped NRs grown along (0 0 2) direction. The light harvesting efficiency of pristine ZnO NRs was enhanced with increase in doping concentration which is due to rise in absorbance as verified by UV–Vis absorption spectroscopy. When used as photoanodes in PEC water splitting under UV illumination, these NR arrays exhibits an enhanced photocurrent density of 2.16 mA cm −2 at 1.2 V vs. Ag/AgCl which is much higher than undoped ZnO NRs (0.103 mA cm −2 ). Cl_Z3 photoanode exhibits a stable photocurrent density even after continuous illumination of 12 h. The significantly improved photoresponse behavior and high photostability with suitable bandgap and high light harvesting efficiency of these photoanodes provides valuable platforms for efficient photoelectrochemical water splitting applications.